Analysis of Price, Brand Awareness, and Brand Image to The Purchase Intention of Pregnancy Pillow (Case Study of Surya Bedsheet) - Delita Kusuma Gading; Dewi Nusraningrum (Universitas Mercu Buana, 2021)
This study was conducted to determine analysis of price, brand awareness, and brand image to the purchase intention of pregnancy pillow (case study of Surya Bedsheet). The object of the research is the mothers and pregnancy women in Indonesia. The data was obtained by using a questionnaire distributed online to 115 respondents. The data was examined with Partial Least Square (PLS) by testing the outer and inner model with a significance level of 0.05 (5%=1.96). The results indicated that price (t-stats=1.134) positive but has no significant influence toward purchase intention, brand awareness (t-stats=2.239), and brand image (t-stats=4.709) are positive and have influences on purchase intention. The highest impact is from brand (t-stats=4.709). It shows that product innovation for pregnancy pillow is an essential consideration for consumers to buy pregnancy pillow. In overview, Surya Bedsheet is a small medium enterprise engaged in the production of baby and mother products that continually upgrade their product and customer service for better serve the customers.Keywords: Price; Brand Awareness; Brand Image; Purchase Intention.